Enhancing Student Interest and Learning Outcomes Fiqh Education in Madrasah Ibtida’iyah through Comic-Based Student Worksheets (LKPD): A Research and Development Approach - Nasution, Wahyuddin Nur; Khadna, Sheilla Fahira; Purba, Risma Br; Khairunnisah, Widya; Nirwana, Nirwana (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Purpose – This study explores the effectiveness of Comic-Based Student Worksheets (LKPD) in enhancing student interest and learning outcomes in Fiqh education at Madrasah Ibtida’iyah. It addresses the gap in conventional teaching methods by integrating visual learning strategies through comics, aiming to captivate students and improve their understanding and retention of Fiqh concepts. Design/methods/approach – Employing a Research and Development (R&D) approach, the study developed a comic-based LKPD and assessed its validity, practicality, and efficacy. The design process followed a meticulous framework to ensure the LKPD’s content was both educationally relevant and engaging. Data were collected through observations, document analysis, and product evaluations, using Likert scales for validity and practicality assessments, as well as pretest-posttest measures for efficacy evaluation. Findings – Findings indicate a significant improvement in students’ interest and learning outcomes, with a notable increase in engagement and academic achievement. The comic-based LKPD not only made Fiqh lessons more interactive but also facilitated a deeper understanding of the subject matter, evidencing the potential of comics in educational material design. Research implications – The implications of this research are twofold. For educators, it underscores the value of incorporating comic-based learning materials to enhance engagement and comprehension. The field of education suggests a novel approach to teaching Fiqh and potentially other subjects, advocating for a broader application of visual learning tools.